Age and gender characteristics of patients with tuberculosis and concomitant comorbid pathologies living in rural areas - A.A. Shapran; N.V. Bagisheva; A.V. Mordyk; M.V. Moiseeva; L.E. Kuchchaeva; M.D. Zakavova; E.S. Arbaev; I.G. Steinborm (LLC "MEDIAFORMAT", 2023)
Tuberculosis, if infected, develops regardless of gender, age, place and living conditions. The development of the disease in individuals with pre-existing comorbid somatic pathology has a mutually aggravating effect on the body as a whole. Aim. The purpose of the study was to analyze the gender and age characteristics of patients with pulmonary tuberculosis and chronic non-infectious diseases in the Omsk district of the Omsk region. Materials and methods. The retrospective study included 161 patients living in the Omsk district of the Omsk region, receiving treatment for tuberculosis at the Omsk Central Regional Hospital. In 123 (76.4%) patients, comorbid somatic diseases of various locations were identified. Results. Based on the analysis of medical records, 170 cases of chronic non-communicable diseases were identified. Most often, gastrointestinal diseases were diagnosed (37.6%) (chronic gastritis, peptic ulcer), almost 90% of them in young and middle age. In second place are diseases of the cardiovascular system. A quarter of the patients were diagnosed with arterial hypertension, coronary heart disease or chronic heart failure, 2/3 in young and middle age, only 10% in old age. In patients with tuberculosis, most CNDs manifested in young and middle age. Conclusions. Mortality is higher among elderly people with pathology of the cardiovascular system, without differences by gender. By gender, mortality in patients with tuberculosis and gastrointestinal diseases is higher among men, without differences in age.